Early survival following in utero myocardial infarction. (23rd July 2018) - Cosgrove, Peter; Modi, Shan; Lawson, Karla; Hancock-Friesen, Camille; Johnson, Gregory
Abstract: Intrauterine myocardial infarction is a rare and frequently fatal diagnosis. It has been presented in the literature only as case reports and short series. We present a case report of a coronary occlusive intrauterine myocardial infarction and survival and present a systematic review of the literature. This is the first summative description of current data on intrauterine and perinatal myocardial infarction. We performed the systematic review based on the guidelines established by the PRISMA statement. Our population of intrauterine and perinatal myocardial infarction included published cases who presented as a live birth within the first 28 postnatal days, and had a diagnosis of myocardial infarction. We conducted descriptive statistics and regression analysis on short-term mortality as the primary outcome. After applying exclusion criteria we described 84 individual cases of myocardial infarction from 63 full-text articles including our own case. Presentation within the first 12 hours was associated with mortality (OR 3.90, p=0.004). Treatment modalities were varied and inconsistently recorded. The aetiologies and comorbidities are varied in our systematic review. We would have a low threshold to perform viral testing, consider anticoagulation early and coronary imaging if feasible. The use of extracorporeal membranous oxygenation may serve as a bridge to cardiac recovery.